Analisis Faktor Penentu Kompetensi Berbasis Karakteristik di Hotel Novotel Karawang - Sofiati, Sofiati; Ansry, Danny Evaju (Sekolah Tinggi Pariwisata AMPTA, 2021)
CHARACTERISTIC-BASED COMPETENCY DETERMINANT ANALYSIS IN THE NOVOTEL HOTEL KARAWANG This study aims to determine the effect of characteristic - based competency in the Novotel Hotel Karawang environment. The sample of this study was 70. Data were collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that part there was asignificant effect between skills on employee competencies, there was a significant effect between training towards on employee competencies, there was a significant effect between attitudes towards employee competencies, and there was a significant effect between motivation on hotel employee competencies Novotel in karawang. Together, the skills, training, attitude, and motivation factors have a significant influence on competency of Novotel Hotel employees in Karawang and motivation has the most the dominant influence on the competency of Novotel Hotel employees in Karawang.